Hegemony of Independent Campus Learning (Antonio Gramsci's Hegemony Study in the Indonesia Education System) - Robin, Patricia; Ronda, Andi Mirza; Napitupulu, Frengki (Academy of Education Journal, 2024)
Freire once revealed how education could liberate with the essence of "free"; truly "free". The existence of opportunities, challenges and demands continues to grow, especially for outsider students whose numbers continue to increase from year to year and need to be reviewed by the government. Through the MBKM, the government as the highest political society holder becomes an agent capable of making elements within it to submit and obey any policy made. The objective of the research is to explore the MBKM program that is proposed as a way out of the educational problem that has long been considered not to be able to meet the needs of the post-graduate student industry and titles as a Bachelor's. The goal of the researchers is to critically uncover and analyze the intellectual agents in the education system that dominate the element of the College through the practice of MBKM. The research method uses qualitative descriptive methods by borrowing the concept of Gramsci that produces descriptive data in the form of written and oral words of people and observable behavior. The results of the research show that the MBKM is an extension of the political practice of the state that is playing its role of power. MBKM is a neo-liberalization of education because the role of the state is increasingly diminishing and replacing with the private role. Students are no longer expected to contribute to the self-development or intellectuality of the nation, but what is important is to serve the private.